Effectiveness of Helminth Therapy in the Prevention of Allograft Rejection: A Systematic Review of Allogeneic Transplantation - Kiss, Michelle; Burns, Heather; Donnelly, Sheila; Hawthorne, Wayne J. (Frontiers in Immunology, 2020)
Background: The unique immunomodulatory capacity of helminth parasites has been investigated as a novel strategy in the prevention of allograft rejection after transplantation. This review was conducted to fully evaluate the specific effects of helminth therapy on allograft survival reported in published studies of animal models of allogeneic transplantation. Method: Following PRISMA protocol guidelines, a literature search was conducted using PubMed, MEDLINE via OvidSP, along with additional manual searches of selected reference lists. Publications describing helminth intervention within allograft transplantation models were screened for relevance to eligibility criteria. Primary and secondary outcomes were extracted using standardised data collection tables. The SYRCLE risk of bias assessment tool was used for quality assessment. Due to heterogeneity of study designs, meta-analysis could not be performed; rather outcomes are presented as a narrative synthesis with concept mapping. This review was registered in PROSPERO with ID: CRD42018097175. Results: The literature search generated 1,443 publications, which after screening for relevance to the eligibility criteria yielded 15 publications for qualitative analysis. All 15 publications reported improvement to allograft survival as a result of helminth therapy. This prolonged allograft survival was not significantly different when helminth-derived products were used compared to live infection. However, the extent of positive impact on allograft survival was noted to be dependent on study design factors such as the chronicity of the live helminth infection, allograft type and the species/genus of helminth selected. Conclusion: Both live and product-based helminth therapy have potential applications as novel immune regulators or adjuncts for the prevention of allograft rejection. However, there were differences in efficacy between different worms and preparations of worm-derived products. Therefore, further studies are required to determine the most appropriate worm for a specific allograft, to elucidate the optimal dose and route of administration, and to better understand the modulation of immune responses that can mediate tolerance.